The Effect of inquiry and Expository Learning Strategy on Students Achievement of Global Perspective Education Subject Viewed From Students Scholastic Potential Of Elementary School Teacher Education Slamet Riyadi University Surakarta - Handinia, Oktiana (Sebelas Maret University, 2016)
The Research purposed to determine the effect ofÂ Inquiry Learning Strategy and Expository Learning Strategy on the Students Achievement of Global Perspective Education Subject viewed From students scholastic Potential consisted of verbal, reasoning, and numerical. The population were 105 Elementary School Teacher Education Students. The sample were 60 students each verbal, reasoning and numerical csholastic potential. The experimental research used 2x3 factorial design tested analysis two ways of varianâs (ANAVA) and followed by scheffe analysis. The hyphoteses analysis showed inqury learning strategy gave a better effect than expository learning strategy to students achievement ( F0 = 29,89 > Ft = 3,17). Students with verbal scholastic potential showed that a higher achievement than students with reasoning scholastic potential and numerical scholastic potential F0 = 38,58 > Ft = 4,02, There is an interaction between learning strategies and scholastic potential to students achievementÂ F0 = 3,50 > Ft = 3,17. Scheffeâs analysis showed that there were notÂ interactions between learning strategies and verbal scholastic potential, There were interactions between inquiry learning strategy and reasoning scholastic potential, There were interactions between learning strategies and numerical scholastic potential, interactions between inquiry learning strategy ang verbal reasoning scholastic potential, interaction between inquiry learning strategy and verbal, reasoning, numerical scholastic potential, There were not interactions between inquiry learning strategy and reasoning, numerical sholastic pontential, interaction between expository learning strategy and verbal, reasoning scholastis potential, interaction between expository learning strategy and reasoning, numerical scholastic potential, and there were not interaction between expository learning strategy and verbal, numerical scholastic potential.Â